Approaches to Sustainable Development in Contemporary Museology - Irene Campolmi (Il Capitale Culturale: Studies on the Value of Cultural Heritage, 2013)
Sustainable development has become a leading value of the 21st century society. Throsby’s and Hutter’s recent studies on inter and intra-generational equity, diversity maintenance and interdependence have demonstrated that sustainability values promote a different perspective on cultural institutions. Particularly, they incite to reorganize the production and consumption patterns, and rethink about the construction of meanings in permanent displays. The paper wants to explore how sustainability principles are an approach to develop a “sustainable museology”, which cares about making visitors more critic and aware of the political, sociological, epistemological and cultural implications that lay behind the making of exhibitions. Museums undertaking a sustainable development of their narrative making processes overpass the Foucauldian idea of art museums as heterotopy, (space of otherness), and approach that of archétopy. This model offers rooms to rethink about narratives as stakeholders’ collective processes capable to “meet the needs of the present without compromising those of the future generations”, as stated in the “Brundtland Commision” Report of 1987. The last display done by the Berlin Neue Nationalgalerie is analysed as a case-study for archétopy.